2022
DOI: 10.4103/1735-5362.350244
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of probiotics and ascorbic acid on bile duct ligation- induced chronic hepatic encephalopathy in rats

Abstract: Background and purpose: Hepatic encephalopathy (HE) is a brain dysfunction caused by acute and chronic hepatic failure. The pathogenesis of HE is unknown, although small intestinal bacterial overgrowth associated with chronic liver damage, hyperammonemia, and oxidative stress are considered major factors for HE. Effective lowering of circulating ammonia and neuroinflammation is the main strategy for preventing and treating HE in cirrhosis. In the present study, the protective effect of probiotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…[127] This model also results in changes to the gut microbiome. [128,129] Rats [130,131] and mice [132] given probiotic treatment to correct dysbiosis induced by BDL showed improvements in liver inflammatory markers and circulating ammonia levels, as well as neuropsychiatric symptoms associated with cirrhosis, such as object discrimination and motor balance. [131] Rats were also used as a model of FMT after BDL in a 2021 study.…”
Section: Surgical Induction Of Cholestatic Cirrhosis By Bile Duct Lig...mentioning
confidence: 99%
See 1 more Smart Citation
“…[127] This model also results in changes to the gut microbiome. [128,129] Rats [130,131] and mice [132] given probiotic treatment to correct dysbiosis induced by BDL showed improvements in liver inflammatory markers and circulating ammonia levels, as well as neuropsychiatric symptoms associated with cirrhosis, such as object discrimination and motor balance. [131] Rats were also used as a model of FMT after BDL in a 2021 study.…”
Section: Surgical Induction Of Cholestatic Cirrhosis By Bile Duct Lig...mentioning
confidence: 99%
“…[128,129] Rats [130,131] and mice [132] given probiotic treatment to correct dysbiosis induced by BDL showed improvements in liver inflammatory markers and circulating ammonia levels, as well as neuropsychiatric symptoms associated with cirrhosis, such as object discrimination and motor balance. [131] Rats were also used as a model of FMT after BDL in a 2021 study. These series of experiments showed that FMT from healthy rats, to rats that received BDL, resulted in reduced hypertension and alleviation of gut dysbiosis but did not significantly impact hepatic fibrosis or expression of liver inflammatory markers [133] (Table 1).…”
Section: Surgical Induction Of Cholestatic Cirrhosis By Bile Duct Lig...mentioning
confidence: 99%
“…There is no definitive cure for this disease, and finding effective substances to prevent neuronal damage is significant. Antioxidant compounds such as gallic acid, naringenin, melatonin, and ascorbic acid have been essential in reducing brain damage caused by BDL [10][11][12]. Oleuropein (OP) is a flavonoid compound extracted from olive leaves and fruit, which has antioxidant and anti-inflammatory properties and can help prevent oxidative injuries [13].…”
Section: Introductionmentioning
confidence: 99%